Workshop Introduction to Transivity System Analysis in Narrative Texts for Students - Santoso, Bernadus Wahyudi Joko; Hasyim, Mohamad Yusuf Ahmad; Pujitriherwanti, Anastasia; Wijaya, Veronica (Universitas Negeri Semarang, 2023)
The competence to analyze students' language is essential and needs to be improved from year to year. So far, in the syntax course, students have only been trained to analyze functions, categories, and semantic roles. The analysis of transitivity has yet to be provided because the language analysis using the Systemic Functional Linguistics (SFL) approach is more complex compared to structural-semantic analysis (functions, categories, and semantic roles). Therefore, this community service aims to introduce the transitivity system to Foreign Language Department students at the Faculty of Language and Arts, Semarang State University, and Indonesian Language Teaching Department students at IAIN Syekh Nurjati Cirebon in short narrative texts. Thus, the effort to improve students' ability to analyze narrative texts with the SFL approach is well-targeted and occurs at the right time, which is before they take Discourse Analysis courses. This community service activity was conducted over two days. On day 1, the team provided a general workshop on the topic, explaining that language in SFL theory can perform three metafunctions: the ideational function, interpersonal function, and textual function. On day 2, the community service students were guided to analyze the seven transitivity elements in narrative texts step by step. The result of this community service is that, on average, students' achievement levels in analyzing the transitivity system in non-narrative texts (independent clauses) are better than in narrative texts. However, the difference is not too significant because it is likely that narrative texts are more complex than SFL analysis of free sentences.